simplifique as expressões algébricas a) 9x + 5y +6y -2x
Soluções para a tarefa
Respondido por
1
Olá!
Soma os semelhantes:
![9x + 5y + 6y - 2x \\ 9x - 2x + 5y + 6y \\ = 7x + 11y 9x + 5y + 6y - 2x \\ 9x - 2x + 5y + 6y \\ = 7x + 11y](https://tex.z-dn.net/?f=9x+%2B+5y+%2B+6y+-+2x+%5C%5C+9x+-+2x+%2B+5y+%2B+6y+%5C%5C++%3D+7x+%2B+11y)
Soma os semelhantes:
Rosiv:
obg
Respondido por
2
9x - 2x = 7x
5y + 6y = 11y
7x 11y
5y + 6y = 11y
7x 11y
Perguntas interessantes
Matemática,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
1 ano atrás
ENEM,
1 ano atrás
ENEM,
1 ano atrás